(untitled) (Al-Farooq Journal of Sciences, 2026)
This study examines the challenges of translating legal texts between English and Arabic, focusing on lexical difficulties and the accurate rendering of legal terminology. It highlights the linguistic, and legal differences that affect legal equivalence and contextual meaning and analyzes the strategies used to address these issues. The study concludes that accurate legal translation requires specialized expertise, professional training, strong knowledge of both legal systems, and the use of reliable electronic dictionaries and parallel corpora.